Expanded insights into the neural component of the activity-based anorexia animal model — morphological changes in the enteric nervous system and altered pain perception - Skowron, Kamil; Stach, Paulina; Kurnik-Łucka, Magdalena; Chwaleba, Katarzyna; Giełczyński, Mateusz; Suchy, Wiktoria; Aleksandrovych, Veronika; Jurczyk, Michał; Kuśnierz-Cabala, Beata; Gil, Krzysztof (Folia Medica Cracoviensia, 2023)
Anorexia nervosa (AN) is an eating disorder characterized by distinct etiopathogenetic concepts that are gradually being linked together to unravel the dominant pathophysiological pathways underlying the disease. Excessive food restrictions, often accompanied by over-exercise and undertaken to lose weight, lead to the development of numerous complications. The biological concept of neurohormonal dysfunc-tion in AN seems incomplete without demonstrating or excluding the role of the enteric nervous system (ENS). Using an animal model of activity-based anorexia (ABA), we conducted the preliminary assess-ment of the ENS structure. Here we show, in preparations stained by immunohistochemistry with anti- ChAT, anti-NOS, anti-PGP 9.5, anti-c-fos, and anti-TH antibodies, a lower density of cholinergic and nitrergic nerve fibers as well as reduced neuronal activity in myenteric plexus. Such structural and functional damage to the ENS may be responsible for a number of gastrointestinal symptoms that worsen the course of the disease. In addition, we expanded the study to address the unresolved issue of mechanical and thermal pain sensitivity in AN. The Von Frey and hot plate tests revealed, that in ABA animals, the pain threshold for mechanical stimulus decreases while for thermal increases. In this way, we have sig-nificantly supplemented the background of AN with potentially observable nervous system changes which may influence the evolution of the therapeutic approach in the future.
Keywords: anorexia nervosa; eating disorders; activity-based anorexia; animal model; enteric nervous system; gut-brain axis; pain perception; pain sensitivity